Corwin Coal Mine, Cape Lisburne, n.d. - Nowell, Frank H., 1864-1950 (1894)
Caption on image: Corwin Coal Mine, Cape Lisbourne, Alaska. F.H. Nowell, Nome, 5136 Cape Lisburne is a promontory, 1500 feet high, on the Chukchi Sea coast, 40 miles northeast of the village of Point Hope on the Arctic Slope. It was discovered and named by Capt. Cook in 1778. (pg. 579) Notes from Donald Orth, Dictionary of Alaska Place Names: Geological Survey Professional Paper 567 (Washington: United States Government Printing Office, 1967) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number